Effect of natural farming, organic farming, and recommended package of practices on yield and economics of irrigated wheat (Triticum aestivum) - ALOK KUMAR BEHERA; C P CHANDRASHEKARA (The Indian Journal of Agricultural Sciences, 2023)
An experiment was carried out on a split-plot design with two uneven controls, viz. four foliar concentrations of cow urine, and jeevamrutha under natural farming which were compared with Organic farming (OF), and Recommended package of practices (RPP) given by University of Agricultural Sciences, Dharwad (UASD). The treatments were replicated thrice. The study found that the UASD RPP recorded significantly higher grain yield, straw yield, gross return, net return, and B:C ratio than OF and natural farming practices. The grain yield reduction in the best treatment (cow urine @50% + jeevamrutha @100%) was 16% lesser than RPP, and 2% higher than OF. However, the cost of cultivation in natural farming with cow urine @50% + jeevamrutha @100% was lesser to the extent of 6.91 and 30.42% than UASD RPP and OF. Hence, the study indicates that irrigated wheat can be grown under UASD RPP followed by natural farming treatment more profitably.